Perancangan Media Kampanye Program “Cegah Stunting, Itu Penting!” oleh Puskesmas Pasirjambu Kabupaten Bandung - Nichi Hana Karlina; Mohamad Hilman Suparman (ArtComm, 2024)
Stunting is a condition of growth failure in toddlers due to chronic malnutrition, resulting in children being too short for their age. UPTK Puskesmas Pasirjambu recorded cases of stunting during the year 2022, with 77 out of 608 toddlers measured for their height experiencing stunting. Although the program "Prevent Stunting, It's Important" has been running for 3 years, the campaign media such as PowerPoint materials, leaflets, or cards about stunting are considered less appealing and still ineffective. This condition certainly poses a barrier to efforts in preventing stunting in that area. Therefore, the campaign media needs to be designed with an informative and appealing design aimed at pregnant mothers in Pasirjambu District. The method used in this design is a qualitative method with data collection techniques through interviews, observations, and questionnaires. The design of this campaign media aims to provide information and knowledge as early as possible to pregnant mothers as a form of concern and awareness in preventing the ongoing stunting.